"Read it in the papers, seen it on TV…": the 1981 Libyan hit squad scare as a case of simulated terrorism in the United States. Issue 1 (2nd January 2016) - Hänni, Adrian
ABSTRACT: This article contributes to the study of political simulations of terrorism as a hyperreality with a historical analysis of the Libyan hit squad scare that haunted the United States over several weeks in late 1981, when the US media and Reagan administration officials warned of an imaginary hit squad of terrorists sent to Washington by Libyan leader Muammar Gaddafi to assassinate President Reagan. Through an analysis of a range of declassified documents, mainly from the Reagan Library, most of which are processed here for the first time, the emergence of the rumour, which was planted in the US media through fabricated intelligence documents, will be traced to a small group of officials within the Reagan administration who tried to gain public support for the US government's policy towards Libya.